IONOSPHERIC STORM OF NOVEMBER 13–14, 2012: SIMULATION RESULTS OF THERMAL AND DYNAMIC EFFECTS - Domnin, I. F.; Katsko, S. V.; Lyashenko, M. V.; Chernogor, L. F. (Видавничий дім «Академперіодика», 2015)
The simulation results of the effects of the Earth upper atmosphere thermal and dynamic conditions disturbances during the strong magnetic storm of November 13–14, 2012 are presented. The magnetic storm has caused a whole package of processes which accompanied plasma, electric and magnetic fields disturbances in different regions of near-Earth space. The occurrence of individual characteristics and general regularities in geomagnetic storms is confirmed.Key words: geospace storm, ionospheric disturbance, incoherent scattering, dynamic and thermal processesManuscript submitted 01.10.2014 Radio phys. radio astron. 2014, 19(4): 336-347 REFERENCES1. DOMNIN, I. F., EMELYANOV,L. Ya., KATSKO, S. V. and. CHERNOGOR, L. F., 2014. Ionospheric Effects of Geospace Storm of November 13–14, 2012. Radio Phys. Radio Astron., vol. 19, no. 2. pp. 170–180 (in Russian). 2. CHERNOGOR, L. F, DOMNIN, I. F., 2014. Physics of Geospace storms. Kharkiv: V. N. Karazin Kharkiv National University Publ. (in Russian). 3. CHERNOGOR, L. F., 2003. Physics of Earth, Atmosphere, and Geospace from the Standpoint of System Paradigm. Radio Phys. Radio Astron., vol. 8, no. 1. pp. 59–106 (in Russian). 4. GRIGORENKO, E. I., PAZYURA, E. I., TARAN, V. I., CHERNOGOR, L. F., and CHERNYAEV, S. V., 2005. Dynamic processes in the ionosphere during a strong magnetic storm on May 30-31G. 2003. Geomagnetizm i Aeronomiya, vol. 45, no. 6, pp. 803–823. 5. SALAH, J. E. and EVANS, J. V., 1973. Measurements of thermospheric temperature by incoherent scatter radar. In: Space Research XIII. Berlin: Academie, Verlag, pp. 268–286. 6. PICONE, J. M., HEDIN, A. E., DROB, D. P. and AIKIN, A. C., 2002. NRLMSISE-00 empirical model of the atmosphere:Statistical comparisons and scientific issues. J. Geophys. Res. Space Phys., vol. 107, Is. A12, pp. SIA15-1–SIA15-16. DOI: https://doi.org/10.1029/2002JA009430 7. BANKS, P., 1969. Thermal structure of the ionosphere. Proc. IEEE, vol. 57, no. 3, pp. 258–281. DOI: https://doi.org/10.1109/PROC.1969.6959 8. SCHUNK, R. W. and NAGY, A. F., 2004. Ionospheres: Physics, Plasma Physics and Chemistry. Cambridge, UK: Cambridge University Press. 554 p. 9. BANKS, P. M., 1966.Charged particle temperatures and electron thermal conductivity in the upper atmosphere. Ann. Geophys., vol. 22, pp. 577–584. 10. DALGARNO, A. and DEGGES, T. C., 1968. Electron cooling in the upper atmosphere. Planet. Space Sci. vol. 16, Is. 1, pp. 125–127. DOI: https://doi.org/10.1016/0032-0633(68)90049-4 11. SERGEENKO, N. P., 1982. Estimates of electric fields during ionospheric disturbances. In.: Ionospheric forecasting. Moscow: Nauka Publ. (in Russian). 12. BRYUNELLI, B.E., NAMGALADZE, A.A., 1988. The ionosphere physics. Moscow: Nauka Publ. (in Russian). 13. DOMNIN, I. F., EMELYANO,V L. YA., LYASHENKO, M. V., KHARYTONOVA, S. V. and CHERNOGOR L. F., 2012.Ionospheric Processes During the Geospace Storm of August 5–6, 2011. Radio Phys. Radio Astron., vol. 17, no. 4. pp. 320–332 (in Russian). 14. GRIGORENKO, E. I., LYSENKO, V. N., TARAN, V. I., CHERNOGOR, L. F., 2003. Radio physical results of research processes in the ionosphere, accompanied by a strong geomagnetic storm of September 25, 1998. Uspehi sovremennoi radioelektroniki. no. 9, pp. 57–94 (in Russian). 15. GRIGORENKO, E. I., LAZORENKO, S. V., TARAN, V. I., and CHERNOGOR, L. F., 2003. Ionospheric wave disturbancesaccompanied by the solar flare and the strongest magnetic storm of September 25, 1998. Geomagn. Aeron. vol. 43, no. 6, pp. 770–787 (in Russian). 16. KATSKO,S. V., DOMNIN,I.F., EMELYANOV,L. Ya., LYASHENKO, M. V., and CHERNOGOR, L. F., 2014. Ionospheric Storm of August 5–6, 2011: Calculation Of Main Effects. Radio Phys. Radio Astron. vol. 19, no. 1, pp. 26–39 (in Russian). 17. DANILOV, A. D., 2013. The reaction of the F region to geomagnetic disturbances (review). Geliogeofizicheskie issledovaniya. no. 5, pp. 1–33 (in Russian). 18. PAZYURA, S. A., TARAN, V. I.,and CHERNOGOR, L. F., 2008, Features ionospheric storm on 4-6 April 2006. Space Science and Technology, vol. 14, no. 1, pp. 65–76 (in Russian). 19. MANSILLA, G. A., 2004.Mid-latitude effects of a great geomagnetic storm. J. Atmos. Sol.-Terr. Phys., vol. 66, no. 12, pp. 1085–1091. 20. MANSILLA, G. A., 2010. Some effects in the upper atmosphere during geomagnetic storms. Adv. Space Res., vol. 47, no. 6, pp. 930–937. 21. SOJKA, J. J., DAVID, M., SCHUNK, R. W. and HEELIS, R. A., 2012. A modeling study of the longitudinal dependence of storm time midlatitude dayside total electron content enhancements. J. Geophys. Res. Space. Phys., vol. 117, is. A2. id. A017000. DOI: https://doi.org/10.1029/2011JA017000